2017
DOI: 10.1093/nar/gkx355
|View full text |Cite
|
Sign up to set email alerts
|

Piwi interacts with chromatin at nuclear pores and promiscuously binds nuclear transcripts in Drosophila ovarian somatic cells

Abstract: Piwi in a complex with Piwi-interacting RNAs (piRNAs) triggers transcriptional silencing of transposable elements (TEs) in Drosophila ovaries, thus ensuring genome stability. To do this, Piwi must scan the nascent transcripts of genes and TEs for complementarity to piRNAs. The mechanism of this scanning is currently unknown. Here we report the DamID-seq mapping of multiple Piwi-interacting chromosomal domains in somatic cells of Drosophila ovaries. These domains significantly overlap with genomic regions tethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 67 publications
0
47
0
Order By: Relevance
“…12). Dam-ID showed that both Piwi and NPCs contacts chromatin at the same regions 31 . In this regard, dNxf1 can localize to nuclear peripheries in which most constitutive heterochromatin resides 13,3234 .…”
Section: Figurementioning
confidence: 99%
“…12). Dam-ID showed that both Piwi and NPCs contacts chromatin at the same regions 31 . In this regard, dNxf1 can localize to nuclear peripheries in which most constitutive heterochromatin resides 13,3234 .…”
Section: Figurementioning
confidence: 99%
“…Later, it was established that ELYS recruits Nup107 complex to kinetochores and hence helps in regulation of Nup107 complex mediated microtubule formation at kinetochores (Gillespie et al, 2007;Mishra et al, 2010;Yokoyama et al, 2014). Importantly, ELYS binds with promoter regions in chromatin and interacts with Mcm-7 helicase to exert control during DNA replication as well as interacts with Piwi for transcriptional regulation (Gillespie et al, 2007;Ilyin et al, 2017). Loss of ELYS induces severe defects in organism development like skeleton loss in Zebrafish, embryonic lethality in mouse, tissue differentiation defects and aging phenotypes (Cerveny et al, 2010;Davuluri et al, 2008;de Jong-Curtain et al, 2009;Gao et al, 2011;Okita et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…We chose Drosophila melanogaster (fruit flies) to address the importance of ELYS in early developmental processes. Although CG14215 has been reported as ELYS in Drosophila (hereafter as dElys) and shown to be present at the nuclear periphery and in association with promoter region on polytene chromosomes, none of these studies characterized dElys for its role in NPC assembly or other cellular processes in vivo (Ilyin et al, 2017;Pascual-Garcia et al, 2017). Here, through genetic, molecular and cellular characterization we report that the dElys plays important roles in the assembly and dynamics of nuclear pore and nuclear lamina functions.…”
mentioning
confidence: 81%
“…Finally, we tested whether Hywi-piRNA complexes physically associate with the somatic RNA targets identified by piRNA mapping, DGE analysis of hywi RNAi animals, and/or degradome sequencing. To this end, we performed RNA-immunoprecipitation (RIP) to isolate Hywi-piRNA-RNA ternary complexes from epithelial Hydra (Ilyin et al 2017). We performed RT-PCR to test for the presence of the following transcripts in our immunoprecipitated complexes: 1) eight TE transcripts that were upregulated in response to hywi knockdown, had a high number of piRNAs mapping, and were identified as targets in the degradome sequencing; 2) seven gene transcripts that were upregulated in response to hywi knockdown and had a high number of piRNAs mapping (one of these was identified as a target in the degradome sequencing) ( Table S3); 3) three gene transcripts that were upregulated in response to hywi knockdown, but did not have a high number of piRNAs mapping; and 4) six gene transcripts that were not affected by hywi knockdown and did not have a high number of piRNAs mapping to act as negative controls.…”
Section: Piwi-pirna Complexes Cleave Te Transcripts In Epithelial Stementioning
confidence: 99%